FABP4 and Metabolite Profile in Lipopolysaccharide-Induced Mice Model Treated with Moringa oleifera Ethanol Leaf Extract - Hanifah, Cenia P.; Sulistiyorini, Ifa; Sumirat, Vanessa A.; Anggraeni, Neni; Putri, Mirasari; Ghozali, Mohammad; Syamsunarno, Mas Rizky A.A (Universitas Padjadjaran, Indonesia, 2023)
Sepsis, a life-threatening organ dysfunction resulting from a dysregulated host response to infection, induces changes in blood cells and metabolic alterations. Fatty acid binding protein 4 (FABP4), a lipid chaperone predominantly expressed in adipose tissue, is modulated in sepsis and may contribute to metabolic and immunologic changes. Moringa oleifera (M. oleifera) leaf extract (MOLE) is known to modulate immune system activity, but its potential for treating acute inflammatory conditions like sepsis remains unclear. This study investigates the ability of MOLE to modulate metabolite and hematological profiles in lipopolysaccharide (LPS)-induced sepsis in mice. Thirty-five male Swiss Webster mice (Mus musculus) were divided into five groups, including healthy control pre-treated with 0.5% carboxymethyl cellulose (CMC), an LPS-induced negative control, an LPS-induced positive control treated with dexamethasone (DMX) 7mg/KgBW/day and two MOLE treatment groups with doses of 5.6 and 11.2 mg/20 gBW. Mice received MOLE pre-treatment for three days before LPS induction. Three hours post-LPS injection, the LPS-induced group exhibited leukopenia (1.4 [0.9-2.5] x109 cells/L) and a 68.3% increase in triglyceride levels. However, the MOLE-treated group showed improved erythrocyte levels compared to the positive control group; [(9.9(9.3-10.0) x1012 cell/L) vs (7.7(7.0-9.0) x1012 cells/L), p<0.05]. The study suggests that MOLE administration may positively impact sepsis conditions, particularly by enhancing RBC levels. Further research with an extended observation period is recommended to address limitations in metabolite level assessment.